Chapter Chemical Detection of Short-Lived Species Induced in Aqueous Media by Atmospheric Pressure Plasma - Gorbanev, Yury (InTechOpen, 2019)
Non-thermal atmospheric pressure plasmas are widely used in biomedical research and clinical applications. Such plasmas generate a variety of reactive oxygen and nitrogen species upon interaction with ambient surroundings. These species further interact with a biological substrate and are responsible for the biomedical effects of plasma. Liquid water is an essential part of any biological systems. Some of the most reactive species induced by plasma in aqueous media are radicals and atoms. Hence, the presence of certain chemical components in a plasma 'cocktail' presents an important task for both understanding and further development of plasma systems with specific purposes. In this chapter, we discuss various methods of detection of the plasma-generated short-lived reactive species. We dissert various plasma-induced radicals and atoms (•OH, O2•−/•OOH, •NO, O), together with non-radical short-lived species (−OONO, O3, 1O2). Electron paramagnetic resonance (EPR) is the most direct method of radical detection in water-based media. Special attention is paid to the limitations of the detection methods, with an emphasis on spin trapping used in EPR analysis.